Muscle Strength and Flexibility in Male Marathon Runners: The Role of Age, Running Speed and Anthropometry - Nikolaidis, Pantelis Theodoros; Del Coso, Juan; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2019)
Most studies on marathon runners focused on physiological parameters determining performance, whereas neuromuscular aspects, such as muscle strength and flexibility, received less attention. Thus, the aim of the present study was to examine the relationship of age, body composition and running speed with muscle strength and flexibility of recreational marathon runners. Men marathon runners (n=130, age 44.1±8.6 years, height 176±6 cm, body mass 77±9 body mass index 24.7±2.6 kg.m-2 and race speed 10.29±1.87 km/h) were separated into eight age groups (<30, 30-35, ..., 55-60, >60 years). Four weeks before competing in a marathon, participants performed the sit-and-reach test (SAR), squat (SJ) and countermovement jumps (CMJ), and four isometric muscle strength tests (right and left handgrip, lifting with knees extended and flexed) providing an index of overall muscle isometric strength in absolute (kg) and relative to body mass values (kg.kg-1 body mass). Afterwards participants competed and finished the Athens Classic Marathon (2017) and the race speed was used as an index of running performance. As an average for the whole sample, SAR was 17.6±8.5 cm, SJ was 24.3±4.2 cm, CMJ was 25.8±4.8 cm, overall muscle isometric strength was 386±59 kg in absolute values and 5.06±0.78 kg/kg of body mass in relative terms. The older age groups had the lowest scores in SJ (p<0.001, ηp2=0.298) and CMJ (p<0.001, ηp2=0.304), whereas no age-related difference in SAR (p=0.908, ηp2=0.022), absolute (p=0.622, ηp2=0.042) and relative muscle isometric strength (p=0.435, ηp2=0.055) was shown. Race speed correlated moderately with relative isometric strength (r=0.42, p<0.001), but not with the other neuromuscular measures (r<0.13, p>0.130). In summary, age-related differences were shown in jumping ability, but not in flexibility and isometric muscle strength. Although these parameters - except relative strength - did not relate to running speed, they were components of health-related physical fitness. Consequently, coaches and runners should consider exercises including stretching and strengthening in their weekly program to ensure adequate levels for all components of health-related physical fitness.